2019
DOI: 10.3389/fphar.2019.00947
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Lanosterol Synthase Up-Regulation in UV-B-Induced Oxidative Stress

Abstract: UV-B radiation may be an important risk factor in cataract etiology. After exposure to UV-B radiation, cells show imbalances in the repair of DNA damage, which induce changes in the levels of certain proteins, including alpha-crystallin, which is the most abundant protein in the lens and crucial for the maintenance of lens transparency. Lanosterol synthase (LSS), an essential rate-limiting enzyme in cholesterol biosynthesis, might play significant roles in oxidative stress and in the maintenance of lens transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…Recently, it was reported that the administration of lanosterol plays a protective role in the early stages of crystallin denaturation and lens epithelial cell apoptosis by oxidative-damage-induced UV-B exposure [7]. Huang et al showed that a combination of lanosterol and hesperetin is effective in delaying selenite-induced cataracts [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that the administration of lanosterol plays a protective role in the early stages of crystallin denaturation and lens epithelial cell apoptosis by oxidative-damage-induced UV-B exposure [7]. Huang et al showed that a combination of lanosterol and hesperetin is effective in delaying selenite-induced cataracts [8].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kang et al reported that lanosterol disrupts the aggregation of human γD-crystallin by binding to the hydrophobic dimerization interface and is likely correlated with oxidative stress processes [6]. In addition, lanosterol can play a protective role during the early stages of crystallin denaturation and lens epithelial cell apoptosis through oxidative-damage-induced UV-B exposure [7]. Huang et al also reported that a combination of lanosterol and hesperetin is effective in delaying selenite-induced cataracts [8].…”
Section: Introductionmentioning
confidence: 99%
“…The present study revealed that Hn was expressed in Hlecs and responded to oxidative stress. The level of roS in Hlecs has previously been reported to be positively associated with the dose of uVB and induced different degrees of oxidative stress in cells (27). The results indicated that 4-12 h after uVB irradiation, Hn expression increased, which was associated with uVB irradiation.…”
Section: Discussionmentioning
confidence: 65%
“…Recent studies utilizing murine models have demonstrated the role of ROS in UV-B-induced insult in a variety of diseases ranging from skin cancer to cataracts. 22,23 Indeed, UV-B overexposure even induces oxidative stress in flora, demonstrating the over-arching risk of ROS overproduction due to UV-B. 24 This prevalent oxidative stressinducing ability of UV-B is, therefore, a key point of focus in the search for therapies to mitigate UV-Binduced injury.…”
Section: Discussionmentioning
confidence: 99%